2016
DOI: 10.1080/19443994.2015.1072064
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion free watermelon (Citrullus lanatus) rind as adsorbent for the removal of lead and copper ions from aqueous solution

Abstract: A B S T R A C TChemically protonated watermelon rind (PWR) was evaluated as a low-cost and efficient adsorbent for the removal of Pb 2+ and Cu 2+ ions from aqueous solution. Protonation of watermelon rind (WR) was carried out with 0.1 M HCl as protonating agent. The adsorption process was found to be spontaneous and exothermic in nature. Kinetic investigations suggest that the present system follows pseudo-second-order kinetic model and rate-limiting step is not chemical reaction. The maximum loading capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…This lack of consistency proved that the rate limiting step was not chemisorptions, even though the data has been an appropriate fit to the pseudo second order kinetic model. Similar kind of observations was reported for the removal of Pb 2+ and Cu 2+ ions by watermelon rind .…”
Section: Resultssupporting
confidence: 87%
“…This lack of consistency proved that the rate limiting step was not chemisorptions, even though the data has been an appropriate fit to the pseudo second order kinetic model. Similar kind of observations was reported for the removal of Pb 2+ and Cu 2+ ions by watermelon rind .…”
Section: Resultssupporting
confidence: 87%
“…e inconsistency in the value of k for varying initial concentration of counter ions suggests that chemical reactions are not the rate-limiting step, even though kinetic data tend to fit well with the pseudo-second-order model. Communications observed were similar to this study for the elimination of Cd 2+ ions by ionic liquid [17] and the removal of Pb 2+ and Cu 2+ ions by Watermelon rind [7].…”
Section: Adsorption Isothermssupporting
confidence: 88%
“…Adsorption is a premier technique found to be a powerful and cost-effective method for the elimination and recovery of heavy metal ions and precious RREs. Many adsorbents such as activated carbon [ 6 ], agricultural waste and by-products [ 7 ], and organic frameworks [ 8 ] are found to be prolific in terms of cost and being ecofriendly; however, the efficiency and regeneration is always a concerning factor. Recently, the development of nanomaterials and ionic liquids has led to a new era of technological advancements in the field of wastewater treatments and recovery of REEs.…”
Section: Introductionmentioning
confidence: 99%
“…Watermelon-based biosorbents were also used to adsorb Pb(II) [22,23]. Akkaya and Güzel [23] found that the optimum conditions using watermelon rind as an adsorbent, were obtained at pH 5, 80 min of contact time and 0.1 g/50 mL solid/liquid ratio.…”
Section: Agricultural Waste Biosorbents For Heavy Metal(oid)s Adsorption 21 Watermelon-based Biosorbentsmentioning
confidence: 99%